Respuesta :
ANSWER
[tex] log_{2}(9 {x}^{3} ) = log_{2}(9 ) +3 log_{2}( {x} )[/tex]
EXPLANATION
We have the logarithmic expression,
[tex] log_{2}(9 {x}^{3} ) [/tex]
Recall the product rule of logarithm,
[tex] log_{a}( MN ) = log_{a}( M) + log_{a}( N ) [/tex]
We apply thus law to get,
[tex] log_{2}(9 {x}^{3} ) = log_{2}(9 ) + log_{2}( {x}^{3} ) [/tex]
Recall again that,
[tex] log_{a}( { M}^{n} ) =n log_{a}( { M})[/tex]
We apply this law too to obtain,
[tex] log_{2}(9 {x}^{3} ) = log_{2}(9 ) +3 log_{2}( {x} )[/tex]
[tex] log_{2}(9 {x}^{3} ) = log_{2}(9 ) +3 log_{2}( {x} )[/tex]
EXPLANATION
We have the logarithmic expression,
[tex] log_{2}(9 {x}^{3} ) [/tex]
Recall the product rule of logarithm,
[tex] log_{a}( MN ) = log_{a}( M) + log_{a}( N ) [/tex]
We apply thus law to get,
[tex] log_{2}(9 {x}^{3} ) = log_{2}(9 ) + log_{2}( {x}^{3} ) [/tex]
Recall again that,
[tex] log_{a}( { M}^{n} ) =n log_{a}( { M})[/tex]
We apply this law too to obtain,
[tex] log_{2}(9 {x}^{3} ) = log_{2}(9 ) +3 log_{2}( {x} )[/tex]